A method for exergetic analysis of a real kraft biomass boiler - Ramos, Vinícius Faria; Pinheiro, Olivert Soares; Ferreira da Costa, Esly; Souza da Costa, Andréa Oliveira (Energy (Oxford), 2019)
Detailed model was proposed in this work for exergy analysis of a real biomass boiler. The model was based on an equilibrium model which uses Gibbs Energy minimization and energy balance to calculate the flue gas composition, the temperature of the furnace and the temperature of the flue gases along the boiler. The exergetic efficiency was calculated by the indirect method, and the exergy destruction in each component of the boiler and each material stream was evaluated. The Gibbs minimization model predicted successfully the complete combustion of the biomass and can be adapted to another thermochemical processes. The exergy analysis results showed that the furnace and the water walls have the higher exergy destruction, accounting for 47% and 30% of the total exergy destruction, respectively. In other parts of the boiler, the exergy destruction was higher in the water and steam flows than in the flue gases, and the results indicate that exergy destruction was higher in streams at lower temperatures. The global exergetic efficiency was 42.47%. •A detailed method for the exergy analysis of a biomass boiler was developed.•Gibbs Energy Minimization was used for the calculation of the flue gases composition and temperature.•The exergy destruction was calculated for each boiler component and separate stream.•Except in the furnace, the water streams showed higher exergy destruction.